The Semiotic Bundle as a reflective tool in pre-service mathematics teachers’ education - Faggiano, Eleonora (Frontiers in Education, 2022)
Contemporary discussions in mathematics education have underlined the role of embodied cognition in mathematics thinking and in conceiving teaching-learning processes as multimodal. In this work, we refer to the Semiotic Bundle approach, according to which teaching-learning processes can be described through the production and evolution of different signs. In this perspective, teacher education should help teachers learn how to pay attention to the multimodality of teaching-learning processes. In this paper, we discuss findings from a pre-service teachers’ professional development experience to show how the Semiotic Bundle can be used as a tool for teachers’ reflection on the teaching-learning processes. The results show that, when pre-service teachers analyzed teaching-learning episodes using the Semiotic Bundle tool, they experienced a reflective activity, through which they became aware of the relationship between the produced signs and the construction of mathematical meanings. The study concludes that the Semiotic Bundle may serve as a reflective tool to be used in pre-service teachers’ education.